ANALISIS FUNGSI LEGENDA TELAGA SARANGAN DI KELURAHAN SARANGAN KEC. PLAOSAN KAB. MAGETAN JAWA TIMUR - Sari Ani (LPPM UNISDA, 2019)
This research was conducted with the aim of describing the functions of legend of lake sarangan stories in Sarangan Village, Kec. Plaosan Kab. East Java Magetan. This research includes qualitative research based on naturalistic approaches. The research data is based on the results of interviews with informants. Data is collected by observation, recording, interviewing and recording methods. Data analysis was carried out in five stages, namely (1) transcribing oral data in written form, (2) summarizing and translating, (3) interpreting. Analysis of the data used in this study is content analysis techniques (conten analysis). The content analysis technique is used in analyzing the function of folklore in the Sarangan lake. The results of the study show that there are functions that include (1) entertainment, (2) institutions of cultural institutions, (3) education, (4) social order, (5) group solidarity, (6) social criticism, (7) pleasant divorce from reality, and (8) potential weapons in society.